NMR assignment of iso-α-acids from isomerised extracts of humulus lupulus L. cones - Khatib, Alfi; Wilson, Erica G.; Kim, Hye Kyong; Supardi, Moses; Choi, Young Hae; Verpoorte, Robert (John Wiley & Sons, Ltd., 2007)
Iso-α-acids are known to contribute to the characteristic bitter taste of beer. Six iso-α-acids were isolated from a carbon dioxide extract of the cones of Humulus lupulus L. by centrifugal partition chromatography followed by separation through β- cyclodextrin binding. This method overcame the low yield issue of most isolation procedures that results from the low stability of these compounds to light and oxygen. Their full identification was performed using one- and two-dimensional NMR spectrometry, including 1H- and 13C-NMR, 1H-1H COSY, HMQC and HMBC and electrospray ionisation mass spectrometry. The results confirmed the structures of the isolated compounds as trans-isocohumulone, cis-isocohumulone, trans-isohumulone, cis-isohumulone, trans-isoadhumulone and cis-isoadhumulone. Epimers can be easily distinguished by observing the chemical shift differences of the H-5, H-1′″, H-2′″ and C-5 signals and the different splitting pattern of H-5 and H-2″.